2013
DOI: 10.1111/ppl.12027
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of calcium/calmodulin‐regulated SlSRs in response to abiotic and biotic stresses in tomato fruit

Abstract: Calcium has been shown to enhance stress tolerance, maintain firmness and reduce decay in fruits. Previously we reported that seven tomato SlSRs encode calcium/calmodulin-regulated proteins, and that their expressions are developmentally regulated during fruit development and ripening, and are also responsive to ethylene. To study their expressions in response to stresses encountered during postharvest handling, tomato fruit at the mature-green stage was subjected to chilling and wounding injuries, infected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 59 publications
3
41
1
Order By: Relevance
“…In response to infection of B. cinerea , all the SlSRs showed upregulated expression patterns in leaf tissues, especially for SlSR1 , SlSR1L , SlSR3L and SlSR4 , whose expression levels were significantly upregulated (Figure 1). The B. cinerea -induced expression patterns of SlSRs in leaf tissues are somewhat different from the previous observation that the expressions of SlSR1 , SlSR1L , SlSR2L and SlSR3 in wounded tomato fruit were suppressed by B. cinerea [30], probably due to the tissue-specific expression feature of the SlSRs [29]. In contrast to the B. cinerea -induced expression patterns of SlSRs , expression of SlSR1 , SlSR1L , SlSR3 and SlSR3L in leaf tissues was upregulated in response to infection of Pst DC3000 (Figure 2).…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…In response to infection of B. cinerea , all the SlSRs showed upregulated expression patterns in leaf tissues, especially for SlSR1 , SlSR1L , SlSR3L and SlSR4 , whose expression levels were significantly upregulated (Figure 1). The B. cinerea -induced expression patterns of SlSRs in leaf tissues are somewhat different from the previous observation that the expressions of SlSR1 , SlSR1L , SlSR2L and SlSR3 in wounded tomato fruit were suppressed by B. cinerea [30], probably due to the tissue-specific expression feature of the SlSRs [29]. In contrast to the B. cinerea -induced expression patterns of SlSRs , expression of SlSR1 , SlSR1L , SlSR3 and SlSR3L in leaf tissues was upregulated in response to infection of Pst DC3000 (Figure 2).…”
Section: Discussioncontrasting
confidence: 92%
“…The Pst DC3000-induced expression of SlSR1 is similar to that of the Arabidopsis AtSR1 , closely related to SlSR1 [29], whose expression was induced by Pst DC3000 [21]. However, infection of Pst DC3000 did not affect the expression of SlSR2 and SlSR3 but suppressed the expression of SlSR4 in leaf tissues (Figure 2), which is contrast to the observation that the expression of SlSR4 in fruit tissues was induced by B. cinerea [30]. Therefore, it seems reasonable that the expression of SlSRs is precisely controlled by complex mechanisms in response to infection from different pathogens.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Follow-up studies showed that CAMTAs belong to a conserved transcription factor family that exists in all the examined multicellular eukaryotes Bouche et al, 2002;Yang and Poovaiah, 2002a;Finkler et al, 2007). The expression of CAMTAs is developmentally regulated (Yang et al, 2012) and responds to different abiotic and biotic signals (Yang and Poovaiah, 2002a;Yang et al, 2013). Target cis-elements for this family are (A/C/G) CGCG(T/C/G) (Yang and Poovaiah 2002a) and (A/C) CGTGT Doherty et al, 2009;Du et al, 2009;Kim et al, 2009b;Galon et al, 2010b).…”
Section: The Best Characterized Cam-regulated Transcription Factors: mentioning
confidence: 99%